2021
DOI: 10.21037/apm-21-429
|View full text |Cite
|
Sign up to set email alerts
|

The role of gut microbiota in the pathogenesis and treatment of acute pancreatitis: a narrative review

Abstract: Gut microbiota and acute pancreatitis Gut microbiotaThe human intestinal tract is inhabited by more than 500 species of bacteria with a population of up to 100 trillion, weighing about 1,271 grams. The common gut bacteria in the human body are mainly composed of 9 phyla, in which 0.1% are facultative anaerobic bacteria dominated by enterobacteria, and 99.9% are obligate anaerobic bacteria

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…These are live microorganisms that confer a health benefit through the inhibition of pathogenic microorganisms, the induction of growth of the mucous layer, and inhibiting apoptosis of epithelial cells. The most used probiotics are Lactobacillus, Bifidobacterium, Streptococcus, and Lactococcus lactis among others [125,126]. Other strategies as antibiotics are not widely used in patients with AP since their prophylactic use does not reduce mortality, and in spite of this, Ahuja et al [127] reported that the pancreatic acini were able to regulate the intestinal microbiota through the secretion of antimicrobials and different pro-inflammatory cytokines, which still must be proven.…”
Section: Gut Microbiome Impact In Apmentioning
confidence: 99%
“…These are live microorganisms that confer a health benefit through the inhibition of pathogenic microorganisms, the induction of growth of the mucous layer, and inhibiting apoptosis of epithelial cells. The most used probiotics are Lactobacillus, Bifidobacterium, Streptococcus, and Lactococcus lactis among others [125,126]. Other strategies as antibiotics are not widely used in patients with AP since their prophylactic use does not reduce mortality, and in spite of this, Ahuja et al [127] reported that the pancreatic acini were able to regulate the intestinal microbiota through the secretion of antimicrobials and different pro-inflammatory cytokines, which still must be proven.…”
Section: Gut Microbiome Impact In Apmentioning
confidence: 99%
“…Их появление связано со снижением уровней воспалительных цитокинов, таких как IL-1-бета, TNF-альфа, CXCL1 и IL-18, и обратно коррелирует с тяжестью панкреатита и системными инфекционными осложнениями. С клинической точки зрения восстановление физиологического состава микробиоты кишечника может быть полезной стратегией для лечения острого панкреатита [48,69,73,139]. Qin и соавт.…”
Section: Issn 2221-2582unclassified
“…It has been found that mastitis in mice leads to a disturbance in their intestinal microbiota, increasing the number of pathogenic bacteria and decreasing the number of beneficial flora in the gut ( Guo et al, 2020 ). One study analysed fecal 16S rDNA diversity in 130 patients with acute pancreatitis and 35 healthy subjects, found that the structure of the gut microbiota was significantly different between the two study groups and was closely related to the systemic inflammatory response and impaired intestinal barrier and the abundance of beneficial bacteria such as blautia was significantly lower in severe patients than in mild and moderate patients ( Lu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%